The effect of feedback on performance and motivation in students taking Research methods for Health Sciences at UNED, Costa Rica (UNED Research Journal, 2016)
Feedback is an important tool in the distance learning process, it helps students to be more critical and analytic. The goal of this study was to measure the effect that feedback has on performance and motivation. We evaluated four tasks in which students had feedback and applied a survey that measured students’ satisfaction with feedback. A significant improvement was found only between the third and the fourth tasks, suggesting that students wait until the end to apply what they learned; other problems include: that feedback was not always positive, unclear instructions about bibliographical references and insufficient time. We recommend strategies that can improve feedback, such as verbal instead of written feedback, co-evaluation and making students reflect, instead of giving them the correct answer.
Keywords: Feedback; evaluate; performance; motivation; learning.